Mathematical analysis and simulations involving chemotherapy and surgery on large human tumours under a suitable cell-kill functional response - Rodrigues, Diego Samuel; De Arruda Mancera, Paulo Fernando [UNESP] (American Institute of Mathematical Sciences (AIMS), 2013)
Dosage and frequency of treatment schedules are important for successful chemotherapy. However, in this work we argue that cell-kill response and tumoral growth should not be seen as separate and therefore are essential in a mathematical cancer model. This paper presents a mathematical model for sequencing of cancer chemotherapy and surgery. Our purpose is to investigate treatments for large human tumours considering a suitable cell-kill dynamics. We use some biological and pharmacological data in a numerical approach, where drug administration occurs in cycles (periodic infusion) and surgery is performed instantaneously. Moreover, we also present an analysis of stability for a chemotherapeutic model with continuous drug administration. According to Norton & Simon [22], our results indicate that chemotherapy is less eficient in treating tumours that have reached a plateau level of growing and that a combination with surgical treatment can provide better outcomes.
Keywords: Chemotherapy; Mathematical modelling; Norton-Simon hypothesis; Tumour; antineoplastic agent; algorithm; biological model; conference paper; drug therapy; human; kinetics; methodology; neoplasm; oncology; pathology; statistical model; Algorithms; Antineoplastic Agents; Drug Therapy; Humans; Kinetics; Medical Oncology; Models, Biological; Models, Statistical; Neoplasms